The Effect of Green Betel Leaves (Piper betle L.) Extract on Wounding Healing in Mice (Mus musculus L.) - Nurul Atika ZarÃ¢â¬â¢ah; Syachruddin Syachruddin; Kusmiyati Kusmiyati (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2021)
Green betel leaf (Piper betle L.) contains secondary metabolites, namely alkaloids, flavonoids, steroids, terpenoids, saponins, tannins. Green betel leaf (Piper betle L.) is widely used for wound healing, especially in rural Indonesians. This study aims to determine the effect of green betel leaves extract (Piper betle L.) on wound healing in mice (Mus musculus L.). The samples were determined using a randomized block design (RBD) using mice (Mus musculus L.) which consisted of three treatment groups using a concentration of 20%, 30%, 40% and one control group. The Measure of the average diameter of the wound was using a ruler on each side of the diameter. The data measurement for the average diameter of wound restriction was analyzed by using the one way. The one way Anova test showed that the sig or p-value is 0.000 <0.05 (at the alpha level of 5%) so that Ho is rejected which indicates that there is an effect of giving green betel leaf extract (Piper betel L.) on wound healing in mice (Mus musculus L.). Based on the results of the LSD or LSD test, it shows that it is not significant / the same because the sig value is 0.074> 0.05, which means that no change occurs in mice when given 30% or 40% extract. Green betel leaf extract (Piper betle L.) has an effect on wound healing in mice (Mus musculus L.).ÃÂ ÃÂ